Proximity to corridors benefits bird communities in vegetated interrow vineyards in Mendoza, Argentina - Andrea Paula Goijman; Agustín Zarco (Avian Research)
Management under ecological schemes and increasing habitat heterogeneity, are essential for enhancing biodiversity in vineyards. Birds provide several contributions to agriculture, for example pest control, recreation and enhancing human mental health, and have intrinsic value. Birds are also ideal model organisms because they are easy to survey, and species respond differently to agricultural land use at different scales. Vegetated borders of crops are key for many species of birds, and distance to the border have been found to be an important factor in vineyard-dominated agroecosystems. We evaluate if there are differences in the bird assemblage, between the interior compared to borders within vineyards, using a hierarchical community occupancy model. We hypothesized that occupancy of birds is greater in environments with greater heterogeneity, which in this study was considered to be contributed by the proximity to vegetated corridors. We expected that vineyard borders close to corridors will have higher bird occupancy than the center of the vineyard. The research was conducted in three vineyards with biodiversity-friendly management practices, in Gualtallary, Mendoza, Argentina. Bird surveys were conducted over three breeding seasons from 2018 to 2020. Occupancy and richness of the bird community was more closely associated with the borders adjacent to the corridors than with the interior of the vineyards, as we initially predicted, although the assemblage of birds did not differ much. More than 75% of the registered species consume exclusively or partially invertebrates. Biodiversity-friendly management and ecological schemes, together with vegetated corridors provide multiple benefits for biodiversity conservation. These approaches not only minimize the use of agrochemicals but also prioritize soil cover with spontaneous vegetation, which supports a diverse community of insectivorous bird species, potentially contributing to pest control.